Pengaruh Model Pembelajaran Tipe Jigsaw dalam Meningkatkan Keaktifan dan Hasil Belajar Peserta Didik Kelas X di SMAN 2 Padang Panjang - Idrus, Hadiyati; Oktaviana, Yulia; Chandra, Artha Nesa (Edusainstika, 2025)
The low engagement of tenth-grade students at SMAN 2 Padang Panjang in conventional teaching methods often results in passive participation during the learning process. Consequently, the learning outcomes of some students tend to be below the Minimum Mastery Criteria. This research was conducted to determine the effect of the Jigsaw cooperative learning model in enhancing the activeness and learning outcomes of tenth-grade students at SMAN 2 Padang Panjang. The method used was a quantitative approach with a quasi-experimental design and a posttest-only control group design. This study was conducted with a population of tenth-grade students consisting of 9 classes. The sample were class XE.2 (experimental group) and class XE.4 (control group), selected through random sampling. The research instruments consisted of an observation sheet for learning activeness and a posttest for learning outcomes. The results indicated that the Jigsaw cooperative learning model positively contributed to student activeness. Student engagement in the experimental group improved across all indicators, with the average percentage of activity 87%, compared to control class which only 56%. The perspective of learning outcomes shows the average posttest score of the experimental group was 86.13, with a completion rate of 90%. This result significantly differed from the control group, the average score of 77.12 with a completion rate of 59.38%. Statistical analysis using the Mann-Whitney U test shows a p-value is 0.0139 (p<0.05), indicating a significant difference between the two groups. In conclusion, the Jigsaw cooperative learning model has a significant effect on enhancing student activeness and learning outcomes.